Risk-Taking and asymmetric learning in boom and bust markets - Kieren, Pascal; Müller-Dethard, Jan; Weber, Martin (Review of finance, 2023)
An increasing number of studies depart from the rational expectations assumption to reconcile survey expectations with asset prices. While surveys are helpful to establish a link between subjective beliefs and investment decisions, precise inference about how investors depart from rational expectations can be challenging without relying on strong assumptions. In this article, we provide direct experimental evidence of how systematic distortions in investors’ expectations affect their risk-taking across market cycles. As mechanism, we identify an asymmetry in how individuals update their expectations across boom and bust markets. The documented mechanism is consistent with survey data and provides important implications for recently proposed asset pricing models.
Vorab online veröffentlicht am 7. November 2022
Gesehen am 18.09.2023
Keywords: Aufsatz in Zeitschrift